1999
DOI: 10.3168/jds.s0022-0302(99)75261-6
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance of Dairy Cows in Various Programmed Breeding Systems Including OvSynch and Combinations of Gonadotropin-Releasing Hormone and Prostaglandin F2

Abstract: In Experiment 1, 308 Holstein cows were assigned randomly to four treatments: 1) GnRH injection followed in 7 d by PGF2 alpha injection, then another GnRH injection 33 h later, and artificial insemination (AI) 16 to 18 h after the second GnRH injection; 2) GnRH injection followed in 7 d by PGF2 alpha injection and AI only after detected estrus; 3) injections of PGF2 alpha 14 d apart, GnRH injection 33 h after the second PGF2 alpha injection, and AI 16 to 18 h later; and 4) injections of PGF2 alpha 14 d apart, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
0
8

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 26 publications
10
64
0
8
Order By: Relevance
“…Eight percent of the cows in OVS were detected in oestrus (by the ALPRO system) and inseminated before the second GnRH injection. Stevenson et al [9] reported that 8 to 16% of cows showed oestrus in the OVS protocol around the time of PGF 2α injection. According to Vasconcelos et al [10] these cows failed to ovulate after the first GnRH injection; they were primarily in the second half of the oestrous cycle when they received the first GnRH injection and exhibited oestrus before the second GnRH injection because the corpus luteum regressed and the cows naturally came into oestrus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight percent of the cows in OVS were detected in oestrus (by the ALPRO system) and inseminated before the second GnRH injection. Stevenson et al [9] reported that 8 to 16% of cows showed oestrus in the OVS protocol around the time of PGF 2α injection. According to Vasconcelos et al [10] these cows failed to ovulate after the first GnRH injection; they were primarily in the second half of the oestrous cycle when they received the first GnRH injection and exhibited oestrus before the second GnRH injection because the corpus luteum regressed and the cows naturally came into oestrus.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, development of treatment programs that can effectively induce oestrus and ovulation in cows can have a major effect on herd reproductive performance. The Ovsynch program was developed allowing cows to be inseminated without the need for oestrus detection and improving reproductive performance during the early postparum period (around 50 d) with no labour investment for detecting oestrous [6][7][8][9]. Such a protocol consists of an injection of GnRH agonist given at random stages of the oestrous cycle followed, 7 d later by an injection of PGF 2α .…”
Section: Introductionmentioning
confidence: 99%
“…Such a scheme has the advantage to synchronize both the CL and follicular waves to inseminate cows at a fixed time. It increases the submission rate of cows for insemination and attenuates deficiencies associated with detection of oestrus (Xu et al, 1997;Stevenson et al 1999). Muruvi et al (2001) also found no difference in three groups of cows synchronized with PGF2α.…”
Section: Resultsmentioning
confidence: 99%
“…in this regard, Pr to cows inseminated were lower for the Ovsynch program compared to conception rates of cows inseminated following the detected oestrus (Burke et al 1996;Pursley et al 1997;Stevenson et al 1999). this lower Pr to inseminated cows of the Ovsynch protocol compared to services made at detected oestrus could be due to insemination of all cows regardless of their cyclicity status and reproductive problems; whereas in the current study, tightly synchronized ovulation between 24 and 32 h following the Ovsynch protocol, and administration of carazolol immediately prior to tai could probably result in numerically lower Pr.…”
Section: Discussionmentioning
confidence: 99%